Kepatuhan Terhadap Zakat Perniagaan: Kajian di Kalangan Pengusaha Stesen Minyak di Pulau Pinang - Nor Adilah, Ahmad Shokori (2011)
The purpose of this study is to examine the business zakah compliance among fuel dealers in Penang. This study is using theory of planned behavior (TPB) as the research framework in order to examine how the independent variables which is consist of attitude, subjective norms and perceived behavioral control, influenced the intention to pay zakah on the business income. Besides, this study also trying to determine the relationship between all the variables mentioned. There are 55 respondents involved in this study while the tests conducted are analysis descriptive and inference. Findings in this study indicate that attitude, subjective norms and perceived behavioral control seen to be at the neutral and highest level. The study also showed that all the three independent variables stated have positive and significant relationship with the dependent variable which is the intention. The multiple regression analysis also found out that attitude, subjective norms and perceived behavioral control have it owns impacts towards the intention to pay zakah on the business income among the dealers.